2014
DOI: 10.5603/ait.a2014.0067
|View full text |Cite
|
Sign up to set email alerts
|

Fluid therapy and perfusional considerations during resuscitation in critically ill patients with intra-abdominal hypertension

Abstract: Intra-abdominal hypertension (IAH) and abdominal compartment syndrome (ACS) are consistently associated with morbidity and mortality among the critically ill or injured. Thus, avoiding or potentially treating these conditions may improve patient outcomes. With the aim of improving the outcomes for patients with IAH/ACS, the World Society of the Abdominal Compartment Syndrome recently updated its clinical practice guidelines. In this article, we review the association between a positive fluid balance and outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 96 publications
0
16
0
Order By: Relevance
“…To avoid excessive fluid overload and abdominal wall edema after the initial period of resuscitation in the critically ill, a rather restrictive fluid management plan is important because there is evidence that a cumulative positive fluid balance by Day 3 is associated with increased morbidity and mortality. 58 Apart from the judicious use of fluid, fluid removal can be achieved by a furosemide infusion and or via renal replacement therapy. 58 Percutaneous catheters are increasingly used to drain intra-abdominal fluids and have shown to successfully reduce IAP levels in patients with secondary ACS caused by pancreatitis, liver cirrhosis with ascites, and after massive fluid resuscitation in patients with burns and sepsis.…”
Section: Management Of Critically Ill Patients With Decreased Acmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid excessive fluid overload and abdominal wall edema after the initial period of resuscitation in the critically ill, a rather restrictive fluid management plan is important because there is evidence that a cumulative positive fluid balance by Day 3 is associated with increased morbidity and mortality. 58 Apart from the judicious use of fluid, fluid removal can be achieved by a furosemide infusion and or via renal replacement therapy. 58 Percutaneous catheters are increasingly used to drain intra-abdominal fluids and have shown to successfully reduce IAP levels in patients with secondary ACS caused by pancreatitis, liver cirrhosis with ascites, and after massive fluid resuscitation in patients with burns and sepsis.…”
Section: Management Of Critically Ill Patients With Decreased Acmentioning
confidence: 99%
“…58 Apart from the judicious use of fluid, fluid removal can be achieved by a furosemide infusion and or via renal replacement therapy. 58 Percutaneous catheters are increasingly used to drain intra-abdominal fluids and have shown to successfully reduce IAP levels in patients with secondary ACS caused by pancreatitis, liver cirrhosis with ascites, and after massive fluid resuscitation in patients with burns and sepsis. 59,60 Different modes and ventilatory pressures may have different impacts, but patient-ventilator asynchrony has probably the most negative effect on AC.…”
Section: Management Of Critically Ill Patients With Decreased Acmentioning
confidence: 99%
“…This chapter focuses on the treatment of IAH/ACS in terms of treatment aimed at reducing IAP. It is important to realize that the presence of IAH/ACS may lead to changes in general ICU management [45]. Respiratory management is affected since studies have shown that higher ventilation pressures (both PEEP and plateau pressures) can be used safely in patients with increased IAP and may be warranted in order to maintain alveolar recruitment [46].…”
Section: Supportive Management Of the Patient With Iah/ Acsmentioning
confidence: 99%
“…Fluid resuscitation may improve blood pressure and cardiac output in patients with IAH but may also further increase IAP, thereby decreasing APP and starting a vicious cycle [72]. Often vasoactive drugs are used to stabilize systemic hemodynamic variables in these patients.…”
Section: The Effect Of Vasopressors On Splanchnic Perfusion In the Sementioning
confidence: 99%
“…As soon as hemodynamic stability is achieved after the resuscitation phase, there should be a transition to a more conservative fluid management and a 'late goal directed fluid removal' (de-resuscitation) [72].…”
Section: Fluid Management In Iah and Gi Dysfunctionmentioning
confidence: 99%